Structure and magnetodielectric properties of titanium substituted barium hexaferrites. Issue 12 (15th June 2021) - Vinnik, D.A.; Starikov, A.Yu.; Zhivulin, V.E.; Astapovich, K.A.; Turchenko, V.A.; Zubar, T.I.; Trukhanov, S.V.; Kohout, J.; Kmječ, T.; Yakovenko, O.; Matzui, L.; Sombra, A.S.B.; et al.
Abstract: BaFe12-x Tix O19 barium hexaferrites up to x = 2.00 were synthesized by the usual ceramic technology. Crystal structure refinement was realized by Rietveld method of powder XRD at room temperature. The unit cell parameters change non-monotonically with titanium concentration. The minimum volume of ~698.75 Å 3 was determined for the x = 1.00. The mechanism of nonequivalent crystallographic positions occupation with titanium cations is established. SEM investigation was shown that the obtained samples are ceramics with a tightly compacted polycrystals (>95%) and average crystallite size of ~5 μm. The Mössbauer investigation confirms such localization of Ti 4+ cations. The field dependence of magnetization at 5 K and 300 K was measured and the main magnetic parameters were determined using the law of approach to saturation. These values decrease almost monotonically with increase in titanium concentration and temperature. The minimum values of these quantities of ~23.4 emu/g, ~1.9 emu/g, 1.2*10 6 Erg/g and ~10 5  Oe were fixed for the x = 2.00 at 300 K. With an increase in the doping concentration, both the magnitude of the electrical ac-resistivity and the temperature of transition to the activation type of conductivity increase non-monotonically. At x = 0.50, the lowest electrical resistivity of ρ ~5.1*10 3 Ohm*cm is observed at room temperature with the electrical transition temperature is Tel ~406.5 K. With an increase in frequency the ac-resistivity decreases, as the value of the band gap. The real part of the permittivity increases constantly with increasing temperature and decreases with increasing frequency for all the compositions. The temperature peak of the tg(d) loss tangent with the doping concentration changes nonmonotonically in magnitude and position. An interpretation of the magnetic and electric states of the substituted BaFe12-x Tix O19 barium hexaferrite is given taking into account the mechanism of occupation nonequivalent crystallographic positions with titanium cations.